The secret of the seal - Davis, Deborah, 1957-; Labrasca, Judy (New York : Scholastics, 1989)
Ten-year-old Kyo, an Eskimo boy, faces a difficult moral choice between friendship for a seal and loyalty to his family.
G5
Keywords: Eskimos -- Juvenile fiction; Eskimos -- Fiction; Seals (Animals) -- Fiction